Optimasi Sediaan Pelembab Ekstrak Kering Kulit Buah Manggis (Garcinia mangostana L.) dengan Kombinasi Asam Stearat dan Trietanolamin sebagai Emulgator - Chomariyah, Nur; Darsono, Farida Lanawati; Wijaya, Sumi (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2019)
Mangosteen is a plant which has a high antioxidant activity. The mangosteen pericarp contains antioxidant compound alpha mangosteen. Beside as an antioxidant, alpha-mangosteen has the potential as skin moisturizer, which gives protection for dry skin condition. The purpose of this research was to know the influence a combination stearic acid and trietanolamin on the physical characteristics and effectiveness. As the results of this researchs optimum formula was obtained using factorial design expert. The formula divided into 4 groups, formula A 10% of stearic acid and 0.1% trietanolamine, formula B was 16% of staric acid and 0.1% trietanolamine, formula C 10% of stearic acid and 0.5% trietanolamine and formula D 16% of stearic acid and 0.5% trietanolamine. Effectiveness and physical quality results were analyzed using one way anova and post hoc tukey with the level of confidence 95%. The results showed that stearic acid as an emulsifying agent have significant effect on the decrease of spreadibility, effectiveness and an increase in pH, viscosity, stickiness and ease for removal. Triethanolamin as an emulsifying agent had significant effect on them decrease of spreadibility, effectiveness and an increase in pH, viscosity, stickiness, and ease for removal. Interaction of both agents had signifficant effect to increase pH, viscosity, and effectiveness and a decrease in spreadibility, stickiness, and ease to removal of moisturizing cream containing the extract mangosteen pericarp. Optimum formula of moisturizing cream dry extract of mangosteen pericarp was obtained, a combination of 14.02% stearic acid and 0.41% trietanolamine as an anionic emulsifying agents.